Мурли: [сказочная повесть] / Анни Шмидт - Шмидт Анна Мария Гертруда (Новые сказочные повести, 2009)
Экземпляры: ф. 1 (20140408) / Инвентарный номер: 98014 / Цена: 70.00 / Авт.знак: Ш 73 / ГРНТИ: 17.82 / ББК: 84(4Нид)